Population, Migration and Climate Change - Wahyuni, Ekawati Sri; Rachmat, Sri Hartini; Nurdinawati, Dina (Sodality: Jurnal Sosiologi Pedesaan, 2020)
The objective of this research is to explain how climate change affects and is affected by population growth and migration. The global analysis will then be followed by a specific study in Indonesia on the relation between population migration and natural disaster events. The research method used a secondary data analysis based on literature review, the 2015 Inter-Census Population Survey (SUPAS) data and 2013 disaster data. To reduce greenhouse gas emissions and ensure the sustainability of the planet's earth, there are three things that should be done, namely to reduce the pace of population growth, to change the pattern of consumption of natural resources, and to increase Earth's carrying capacity by using technologies and innovations. Migration is mostly caused by economic needs, while migration due to disaster events is very small. Migration data records permanent migration type, while the disaster-affected population usually migrates on the temporary bases. The BPS-Statistics Indonesia and the National Disaster Management Authority should have some agreement on defining disasters, including climate change induced-disasters, and on how to collect and store data on the number of people impacted by each of them.